Slavery, Resistance, and Queerness in the Reconstruction Era: Masculinities in American South Plantations - V Harinisri; Vineeth Radhakrishnan (Social Sciences and Humanities Open)
Concerning the masculine paradigm as a target study, this paper analyses the intersectional matrix underlying the socio-political landscape of the American South plantations. Nathan Harris, an American novelist, proposed a fictional discourse in the light of post-emancipation politics that prevailed in the American South during the mid-nineteenth century through his novel, The Sweetness of Water (2021). It depicts the life of two liberated Black slaves namely Prentiss and Landry, working in the peanut plantation of George Walker, a White planter, to achieve their aim of leading an independent life. Beyond featuring the hierarchical conditionalities embedded in post-slavery, this text embodies a novel portrayal of the queer community and its subaltern positionality in a patriarchal hegemonic white society. Consequently, this article provides a sociological study of masculinities involved in the American South plantations with special reference to their societal roles. In the wake of the reconstruction era, this intersectional adjudication of plantation masculinities results in acknowledging ‘gayness’ as a form of White resistance to hegemonic White patriarchy along with advocating the emancipated journey of Prentiss as an absolute indication to emerge oneself as a Black abolitionist.